A new serotyping method for Klebsiella species: evaluation of the technique. Issue 4 (April 1976) - Riser, E; Noone, P; Bonnet, M L
Abstract : A new indirect fluorescent typing method for Klebsiella species is compared with an established method, capsular swelling. The fluorescent antibody (FA) technique was tested with standards and unknowns, and the results were checked by capsular swelling. Several unknowns were sent away for confirmation of typing, by capsular swelling. The FA method was also tried by a technician in the routine department for blind identification of standards. Fluorescence typing gives close correlation with the established capsular swelling technique but has greater sensitivity; allows more econimical use of expensive antisera; possesses greater objectivity as it requires less operator skill in the reading of results; resolves most of the cross reactions observed with capsular swelling; and has a higher per cent success rate in identification.